Síndrome do nevo de Becker Becker nevus syndrome - Fabiane Eiras Cosendey; Nayibe Solano Martinez; Gabriela Alice Bernhard; Maria Fernada Reis Gavazzoni Dias; David Rubem Azulay (Sociedade Brasileira de Dermatologia, 2010)
A síndrome do nevo de Becker é considerada um fenótipo caracterizado pela presença fundamental do nevo de Becker associado à hipoplasia mamária unilateral ou a outras alterações cutâneas, esqueléticas e/ou musculares. Geralmente, surge ao nascimento, aumenta significativamente na adolescência e é uma das síndromes que constituem a síndrome do nevo epidérmico. O artigo relata o primeiro caso da literatura brasileira da síndrome do nevo de Becker em uma paciente de 14 anos com associação de nevo de Becker, hipoplasia mamária unilateral e escoliose. Becker nevus syndrome is a phenotype characterized by the fundamental presence of Becker's nevus with ipsilateral hypoplasia of the breast or other skin, skeletal and/or muscular disorders. This syndrome generally originates at birth, intensifies significantly in adolescence and is one of the syndromes that constitute epidermal nevus syndrome. To the best of our knowledge, this is the first case published in the Brazilian literature of Becker nevus syndrome associated with Becker's nevus, ipsilateral breast hypoplasia and scoliosis in a 14-year-old girl.